1. EVALUATION AND COMPARISON OF THE CONCORDANCE BETWEEN THE LINE PROBE ASSAY AND BACTEC MGIT 960 SYSTEM IN DETERMINING RESISTANCE TO ISONIAZID AND RIFAMPICIN AT THE CENTRAL LUNG HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate and compare the concordance of the Line Probe Assay (LPA) method and the BACTEC MGIT 960 system in determining resistance to Isoniazid (INH) and Rifampicin (RMP).Subjects and methods: This descriptive study included 480 patients suspected of tuberculosis who visited the Central Lung Hospital from January 1, 2023 to September 30, 2023, and underwent simultaneous testing for INH and RMP resistance using both the LPA and BACTEC MGIT 960 methods.Results: For INH: out of 480 patients, 467 patients underwent concurrent resistance testing for INH using both the LPA and BACTEC MGIT 960, with 13 results where INH resistance could not be determined by the LPA method. The results showed a sensitivity of 97.9%, specificity of 99.4% and accuracy of 98.9%, with a discordant rate of 5/467 (1.1%). For RMP: out of 480 patients, 478 patients underwent simultaneous resistance testing for RMP using both methods, with 2 results where RMP resistance could not be determined by the LPA method. The results showed a sensitivity of 94.4%, specificity of 98.9% and accuracy of 98.5%, with a discordant rate of 7/478 (1.5%).Evaluation of discordant results: among the 11 discordant strains (out of 12 total discordant strains), further testing (including DST), GeneXpert MTB/XDR, and GTT) was conducted. For INH resistance: 5/5 discordant strains underwent additional testing. Of these, 2 LPA-resistant strains were INH-sensitive by DST, with one sensitive and one resistant by GTT and GeneXpert MTB/XDR; 3 LPA-sensitive strains were INH-resistant by DST, but GTT and GeneXpert MTB/XDR were INH-sensitive and resistant, respectively. Two resistant strains were confirmed resistant by GTT and GeneXpert MTB/XDR. For RMP: 6/7 discordant strains underwent additional testing. Of these, 5 LPA-resistant strains were RMP-sensitive by DST, with 4/5 showing RMP resistance using GeneXpert MTB/RIF and GTT (mutation at the borderline resistance level), and 1/5 strain could not be cultured. Two LPA-sensitive strains were RMP-resistant by DST, with GTT-resistant and GeneXpert MTB/RIF-sensitive, exhibiting a mutation outside the hotspot region (81bp) of both LPA and GeneXpert MTB/RIF.
Keywords: Rifampicin; Isoniazid; BACTEC MGIT 960; Line Probe Assay